NetworkPrioritizer: a versatile tool for network-based prioritization of candidate disease genes or other molecules - Kacprowski, Tim (Oxford University Press, 2013)
Summary: The prioritization of candidate disease genes is often based on integrated datasets and their network representation with genes as nodes connected by edges for biological relationships. However, the majority of prioritization methods does not allow for a straightforward integration of the user’s own input data. Therefore, we developed the Cytoscape plugin NetworkPrioritizer that particularly supports the integrative network-based prioritization of candidate disease genes or other molecules. Our versatile software tool computes a number of important centrality measures to rank nodes based on their relevance for network connectivity and provides different methods to aggregate and compare rankings. Availability: NetworkPrioritizer and the online documentation are freely available at http://www.networkprioritizer.de. Contact: mario.albrecht@mpi-inf.mpg.de